Electrochemical biointerfaces based on carbon nanotubes-mesoporous silica hybrid material: Bioelectrocatalysis of hemoglobin and biosensing applications - Eguílaz Rubio, Marcos (2018)
We are reporting a novel biosensing platform based on a hybrid nanomaterial that combines the advantages of Nafion-coated multiwalled carbon nanotubes (MWCNTs) and mesoporous silica MCM41 nanoparticles functionalized with hemoglobin (Hb). MWCNTs-MCM41-Hb hybrid bioconjugate was characterized by scanning electron microscopy (SEM), UV–vis spectroscopy and electrochemical techniques after deposition at glassy carbon electrodes (GCE). The combination of the high surface area, biocompatibility and protein loading capacity of MCM41 nanoparticles and the high surface area and catalytic properties of MWCNTs allowed the direct electron transfer (DET) between Hb and the electrode surface. The electron transfer rate constant (k) and the surface coverage of electroactive Hb (ΓHb) were 5.2 s−1 and 4.7 × 10−10 mol cm−2, respectively. The GCE modified with the nanostructured architecture (GCE/MWCNTs-MCM41-Hb) was successfully used as a third-generation biosensor for the highly sensitive and selective quantification of nitrite (NO2 -) and trichloroacetic acid (TCA) by taking advantage of the excellent biocatalytic activity of Hb and the efficient direct charge transfer of the heme group.